2009
DOI: 10.1086/596605
|View full text |Cite
|
Sign up to set email alerts
|

Two Time-Series Analyses of the Impact of Antibiotic Consumption and Alcohol-Based Hand Disinfection on the Incidences of Nosocomial Methicillin-ResistantStaphylococcus aureusInfection andClostridium difficileInfection

Abstract: In 2 multivariate time-series analyses, we were able to show the impact of hand hygiene and antibiotic use on the incidence of nosocomial MRSA infection, but we found no association between hand hygiene and incidence of CDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
2
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 27 publications
6
99
2
8
Order By: Relevance
“…The use of broad-spectrum ␤-lactams, cephalosporins, fluoroquinolones, clindamycin, and macrolides has been associated with increasing CDI incidence (30)(31)(32). Through the study period, there were no significant changes in the consumption of these antibiotics, and, although infectious disease consultants were regularly involved in antibiotic therapy prescribing for infected patients in all wards, no antimicrobial stewardship programs were implemented at that time.…”
Section: Discussionmentioning
confidence: 99%
“…The use of broad-spectrum ␤-lactams, cephalosporins, fluoroquinolones, clindamycin, and macrolides has been associated with increasing CDI incidence (30)(31)(32). Through the study period, there were no significant changes in the consumption of these antibiotics, and, although infectious disease consultants were regularly involved in antibiotic therapy prescribing for infected patients in all wards, no antimicrobial stewardship programs were implemented at that time.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the C. difficile incidence increased following ABHR implementation (five new cases compared to zero cases in the preceding 12 months), but that study was limited to one small ward in a single institution and, therefore, was insufficiently powered to allow firm conclusions. Several more recent and larger in vivo studies evaluating CDI incidence following ABHR implementation have been performed (26,94,170,200,184,199 (185). The procurement of soap and ABHR and hospital bed occupancy data were monitored in relation to quarterly mandatory reports of methicillin-resistant Staphylococcus aureus (MRSA)/methicillin-sensitive S. aureus (MSSA) bacteremia and CDI.…”
Section: Alcohol-based Hand Hygiene and Risk Of CDImentioning
confidence: 99%
“…The CDI incidence did not increase despite increased ABHR usage (185). In a recent study, Kaier et al built a multivariate regression model to identify the dynamic relationship between antibiotic exposure, ABHR, and the incidence of MRSA and CDI (94). The increased usage of ABHR over the 44-month study period negatively impacted MRSA incidence but did not correlate (positively or negatively) with CDI incidence (94).…”
Section: Alcohol-based Hand Hygiene and Risk Of CDImentioning
confidence: 99%
“…A number of studies have shown that improvements in hand hygiene are associated with lower healthcare-associated infection rates, and/or reductions in MDRO transmission and acquisition. [7][8][9][10] Nonetheless, compliance with hand hygiene recommendations is often poor, with studies reporting rates as low as 20 -30%. [11][12][13] The adequate disinfection of hands is easily accomplished by using an alcoholic hand rub, with or without additional disinfectants, e.g.…”
Section: Prevention Of Transmissionmentioning
confidence: 99%